Assistive Technology to Assist the Visually Impaired in the Use of ICTs: A Systematic Literature Review - Zen, Eliana; Siedler, Marcelo da Silveira; da Costa, Vinicius Kruger; Tavares, Tatiana Aires (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
CONTEXT: Assistive Technology refers to a set of resources and services designed to help people with disabilities, providing or expanding their skills, enabling they to carry out activities with comfort and autonomy. PROBLEM: For visually impaired, the AT can guarantee access to ICTs, as resources such as screen and mouse may not be useful. In world, an estimated 285 million people are visually impaired, 39 million being blind. METHODOLOGY: This work describes a Systematic Literature Review, seeking to identify, analyze and interpret works related to AT developed to help visually impaired in the use of systems. INFORMATION SYSTEMS THEORY: Was based on Theory of Interactive Media Effects, who argues that the characteristics of the media, as well as the source and content of the messages, affect the engagement and interaction of individuals involved in communication. SUMMARY OF RESULTS: 108 articles related to AT developed for visually impaired during an interaction with ICTs were obtained. Reading these works, select 12 articles related to learning computer programming and the use of software development tools by visually impaired. It was found that most of the TA resources developed focus only on the extension of the visual interface. CONTRIBUTIONS: The main limitations of the TA to access the resources available in systems for visually impaired, based on RSL, are considered. IMPACT ON SI AREA: Works related to the learning of concepts related to computer programming and software development tools for the visually impaired are analyzed, as well as the contributions, opportunities and challenges related to the development of AT to promote accessibility of these users in Information Systems.